Islamic banking system as a unique phenomenon of the world banking system - Сидоров, Вадим; Гайдей, Никита (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism)
This article analyses the Islamic banking system as a unique phenomenon of the world banking system. The basis for the analysis is the Islamic banking system. The article studies in the historical origins of the pre-Islamic period, the initial Islamic period and the current period of economic idea of the Islamic countries. The article shows the goal of Islamic banks, describes the essence of the Islamic banking system of philosophy, the relationship of Islamic banks with the religion of Islam; consideres such a unique concept as «rib» and «Sharia», making the Islamic banking system a unique one.